Comparison of Characteristics and Survival Rates of Resectable Pancreatic Ductal Adenocarcinoma according to Tumor Location - Min Kyu Sung; Yejong Park; Bong Jun Kwak; Eunsung Jun; Woohyung Lee; Ki Byung Song; Jae Hoon Lee; Dae Wook Hwang; Song Cheol Kim (Biomedicines, 2021)
The impact of tumor location on patient survival in pancreatic ductal adenocarcinoma (PDAC) remains controversial. This study investigated the association between primary tumor location and survival rates for resectable PDAC. Additionally, we assessed if this association remains consistent across categories of the Tumor-Node-Metastasis staging system. We analyzed 2471 patients who underwent surgical resection between 2000 and 2018 at a single center. Subgroup analysis was performed according to the Tumor-Node-Metastasis staging system. Among the group, 67.9% (1677 patients) had pancreatic head cancer (PHC) and 32.1% (794 patients) had pancreatic body/tail cancer (PBTC). Patients with PHC had worse overall survival and worse disease-free survival than those with PBTC. Patients with PHC had worse survival in stage IB and stage IIB than those with PBTC. No significant difference was observed for stages IA, IIA, and III. Multivariate analysis showed that elevated CA 19-9, mGPS, a longer hospital stay, complication, accompanying vein resection, larger tumor size, worse differentiation, higher TNM stage (stage IIB, III, IV), presence of LVI, and positive resection margin were risk factors for poor survival after resection. In resectable PDAC, patients with PHC had worse overall and disease-free survival than those with PBTC. However, tumor location was not an independent prognostic factor for PDAC.